Inefficient complementation activity of poliovirus 2C and 3D proteins for rescue of lethal mutations. - Teterina, N L (1995)
Poliovirus (PV) 2C protein is a nonstructural polypeptide involved in viral RNA replication, whose biochemical activity(ies) in this process has not been defined. By using site-directed mutagenesis, it was shown previously that disruption of nucleotide-binding motifs present in this protein abolished viral RNA synthesis (C. Mirzayan and E. Wimmer, Virology 189:547-555, 1992; N. L. Teterina, K. M. Kean, E. Gorbalenya, V. I. Agol, and M. Girard, J. Gen. Virol. 73:1977-1986, 1992). We have tested whether PV 2C or 2BC protein provided in trans could rescue the replication of these mutated genomes. Rescuing proteins were provided either by cotransfection with helper chimeric PV-coxsackievirus genomes or by expression in cells with a vaccinia virus-T7 RNA polymerase transient-expression system. We report here that replication of mutated RNAs genomes was poorly supported in trans both by helper genomes and by expressed 2C or 2BC proteins. Similarly, very inefficient complementation was observed for two mutated genomes with lethal lesions in 3D polymerase coding sequence. Our results indicate that poliovirus RNA replication shows marked preference for proteins contributed in cis.